Sclerorhachis Platyrachis (Boiss.) Podlech Ex Rech. F.: an Indigenous Medicinal Plant from Northeastern Iran; Essential Oil Composition, Total Flavonoid Content and Antioxidant Activity - Hashem Akhlaghi (Journal of Chemical Health Risks, 2015)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 9.5pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: FA;">In this study, the essential oil obtained by hydrodistillation of the aerial parts of Sclerorhachis platyrachis (Boiss.) Podlech ex Rech. f. (Compositae), growing wild in Sabzevar, Khorasan Razavi Province (Iran), was analyzed by GC and GC/MS. The total yield of volatiles was 0.38% (w/w). Sixty- three compounds representing 89.2% of the aerial parts oil were identified. The main components of the oil were β-pinene (17.5%) and γ-terpinene (15.4%). The oil was rich in monoterpenoids, and among them, monoterpene hydrocarbons (48.7%) predominated over oxygenated monoterpenes (11.8%). The total flavonoid content of different extracts of the plant was in the range 52.4-172.3 mg/g, with the maximum amount being in the methanol extract. The antioxidant activities of the extracts were also measured based on radical scavenging activity of antioxidants using the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) method. The results showed that IC50 values of extracts of S. platyrachis are higher than for the standard synthetic antioxidants, BHT, ascorbic acid and gallic acid.<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->